Pengaruh pola asuh otoriter terhadap self concept pada remaja - Tamami, Abi Syamsudin (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the influence of authoritarian parenting on adolescent self-concept. The research was conducted with a quantitative approach using a correlational method on 156 junior high school students in Malang Regency. Data were collected through PCRQ (Parent-child relationship questionnare) and AF5 self-concept scale, which were then analyzed using regression test, t-test, and ANOVA. The results showed that authoritarian parenting has a significant influence on adolescents’ self-concept through linear regression analysis (F = 7.910, Sig. = 0.006), although t-test and ANOVA did not show significant differences. Most respondents showed low levels of authoritarian parenting and moderate self-concept. The discussion revealed that social, environmental and cultural factors influence adolescents’ self-concept, demonstrating the complexity of the relationship between parenting and psychological development. This study suggests the need for a multidimensional approach in understanding the impact of parenting and the development of programs that support the development of adolescents’ self-concept through adaptive social and educational support.